Effects of acute and moderate caffeine doses on sport climbing performance: a randomized controlled trial - Ruiz-López, A.; Montalvo-Alonso, J. J.; Martín-Rivas, I.; del Val-Manzano, M.; Ferragut, C.; Valadés, D.; Barrios-Egea, M.; Gonzalo-Encabo, P.; Pérez-López, A. (Nutrients, 2026)
Background/Objectives: Caffeine is a well-established ergogenic aid in many strength- and endurance-based sports, but its efficacy in sport climbing remains underexplored despite the sport`s unique physical demands on grip strength, power, and muscular endurance. Therefore, this study examined the acute impact of a low caffeine dose (3 mg/kg) on climbing-specific performance, including pull-up and grip tests, in intermediate-advanced climbers.